(untitled) (The Agriculturists, 2010)
Rice farmers investment on irrigation alone accounts the lion’s share of total production cost. Alternate wetting & drying (AWD) method has emerged as a new technique of irrigation in Bangladesh as water saving irrigation technique. A study was undertaken with a view to verify the differences in water delivery, energy consumption and the relative economics of AWD method and conventional irrigation practice. Data were generated through sample survey in three production environments namely Kustia, Rangpur and Feni where field experiments were conducted to validate the AWD method. Data were generated using pre-designed questionnaire. Mainly descriptive statistics and partial budgeting technique were used in analyzing the data. The analysis revealed that on an average, the sample plots under AWD method required about 30% less water in growing MV Boro rice in all the study areas compared to conventional irrigation of maintaining continuous ponding water. The use of less irrigation was associated with the reduction of irrigation cost by 12 to 15% implying a clear advantage of AWD irrigation to the resource poor farmers. Almost 80% of the sample farmers in Kustia and Rangpur opined that the use of AWD method would also be conducive to increase MV Boro yield to some extent. Partial budget analysis further implied that use of AWD method would render an eventual profit of Tk 4224/ha for adopting the newly emerged irrigation technique instead of using the conventional irrigation.